Analisis Teoretis Atas Hubungan Antara Kepuasan Kerja Dan Kinerja Karyawan: Sebuah Studi Literatur - Rindianti, Desi; Nazwar, Muhammad Naufal; Safirah, Elza; Jusma, Jusma; Ginting, Chrisdayanti Br. (Annusfy : Journal of Multidisciplinary Research, 2025)
This study analyzes the relationship between job satisfaction and employee performance through a literature review of publications from the last ten years (2015–2024). The review results indicate that job satisfaction has a positive impact on performance, both on task performance and extra-role behavior. This relationship is also influenced by factors such as motivation, organizational commitment, and leadership style. In addition to finding consistency in empirical findings, the study identifies a research gap in methodologies still dominated by quantitative methods and the limited sectors studied. This study provides a theoretical basis for the development of further research and human resource management practices.